A Study on Design Appeal of Green Packaging in China - Wang, Lu; Mohamed, Fauzi Naeim (South Asian Journal of Social Sciences and Humanities, 2024)
This quantitative study examines the relationship between consumption functionality and green  packaging dimensions among 484 consumers in China. The data was analyzed using SPSS and  AMOS to test the impact of consumption functionality on product meaningfulness and  willingness to purchase, as well as the mediating role of green packaging. As packaging has  evolved to add functional, emotional and social value to products, influencing brand image,  this study investigates the design appeal of green packaging. The aim is to determine how  consumption functionality affects product meaningfulness and willingness to purchase green  packaged products, and whether green packaging mediates these relationships. The variables  studied include consumption functionality, product meaningfulness, willingness to purchase,  and green packaging components such as symbolic, economic and altruistic values. The  literature review examined prior research on the impacts of consumption functionality on  product meaningfulness and purchase willingness. It also covered studies on the symbolic,  economic and altruistic values of green packaging and its potential mediating effects. The  results provide insights into Chinese consumer responses to green packaging, specifically the  mechanisms by which consumption functionality and green packaging influence product  meaningfulness and willingness to purchase. This helps marketing practitioners determine  effective positioning and messaging approaches for green packaged goods. It provides  guidance on tactical elements like packaging design. The findings can shape creative strategies  for brands looking to leverage green packaging appeals among Chinese consumers. Further  research can build on this study to deepen knowledge in this emerging area as the popularity  of sustainable packaging grows.
Keywords: marketing strategy; packaging design; consumer research; sustainable packaging